OPTIMAL DESIGN OF THERMO-OPTIC DEVICES ON THE SILICON-ON-INSULATOR PLATFORM - Thanh, Le Trung (Vietnam Journal of Science and Technology, 2012)
A novel design of devices based on the thermo-optic effect in silicon on insulator (SOI) waveguides is presented. In order to evaluate accurately the temperature distribution and speed of the device, the heat transfer equation is to be solved numerically. It will be shown in this paper how the new thermo-optic waveguide structure, in which air trenches are made, can improve the performance of the thermo-optic device. In addition, a new formula for calculating the phase shift induced by the thermo-optic effect is proposed. Keyword. Thermo-optic effect, silicon on insulator, optical devices